PENGARUH EDUKASI GIZI TERHADAP PENGETAHUAN, SIKAP DAN KEPATUHAN DIET PENYANDANG DIABETES MELITUS TIPE II PESERTA PROLANIS DI PUSKESMAS PAMOTAN KABUPATEN REMBANG - Risca Ariyana; Sri Noor Mintarsih; Dyah Nur Subandriani (JURNAL RISET GIZI, 2018)
Background : prevalence of diabetes mellitus around the world has increased significantly, including in Indonesia. Nutrition education is one of the main pillars of diabetes mellitus management to improve knowledge and attitude as a basis for improvement of nutritional behavior of diabetic client. Objective : to investigate the effect of nutrition education on the knowledge, attitude and dietary adherence of Prolanis’s type 2 diabetes mellitus clients at Puskesmas Pamotan. Methods : this research usedquasi experimental method with pre and post test group control design. The samples of research consisted of 44 respondents, and divided into intervention group (22 respondents) and control group (22 respondents). The sampling technique usedsimple random sampling. Data collection used questionnaire of respondent characteristics, knowledge of DM diet, attitude about DM diet and food recall form 2 x 24 hours. Data were analysed by using mann-whitney test. Result : there were different in changes  ofknowledge and attitude significantly with p-value 0,001 and 0.039 between treatment and control group, and there were no differentin change of dietary adherence between  treatment and control group(p-value 0,081). Conclusion : nutrition education can improve knowledge and attitude of diabetic client , whereas on dietary adherence there was an increase but not significant